An Overview of Stress Levels on Fishermen on The Payangan Coastal Jember - Nurul Izzah Regita Cahyani; Retno Purwandari; Kholid Rosyidi Muhammad Nur; Anisah Ardiana; Alfid Tri Afandi (Nursing and Health Sciences Journal (NHSJ), 2022)
Indonesia is a country known as a maritime country whose majority of the population works as fishermen. Most of Indonesia's territory is dominated by water areas and is dominated by fisheries and marine activities so many workers work in the fisheries and marine sector. Fisherman workers have different challenges and problems from other workers. This research, which was conducted on the Payangan coastal of Jember Regency, purpose to describe the level of Stress on fishermen in the Payangan coastal area of Jember Regency. The data collection method used in this study used a questionnaire distribution method with fishermen by asking questions about Stress levels using the PSS (Perceived Stress Scale) questionnaire consisting of 10 question items. The number of respondents in this study in 74 fishermen who live in the coastal area of Payangan Beach, Jember Regency and meet the criteria determined by the researcher. The results of this study obtained the results of calculations and data analysis showed that as many as 66 respondents 89.19% experienced moderate Stress levels and as many as 8 respondents 10.81% experienced severe Stress levels. This research is expected to help describe the level of stress on fishermen workers in the coastal area of Payangan, Jember Regency. Stress can occur due to unresolved matters, especially matters related to fishing workers. From this statement, the researcher assumes that social and family support is very important to overcome the moderate Stress experienced by fishermen workers.